Interactions of three soil bacteria species with phyllosilicate surfaces in hybrid silica gels. Issue 1 (2nd April 2014) - Oulkadi, Djihad; Balland‐Bolou‐Bi, Clarisse; Billard, Patrick; Kitzinger, Geraldine; Parrello, Damien; Mustin, Christian; Banon, Sylvie
Abstract To simulate iron consumption in soils, iron leaching from silicate minerals due to three heterotrophic bacterial strains and a chemical treatment was studied using hybrid silica gel (HSG) doped with two phyllosilicates, nontronite (NAu‐2) or low‐iron‐content montmorillonite (SWy‐2). HSG methodology, a novel way of separating bacteria cells from a colloidal mineral source, consisted in embedding colloidal mineral particles into an amorphous porous silica matrix using a classical sol‐gel procedure. Pantoae agglomerans PA1 and Rahnella aquatilis RA1 were isolated from silicate‐rich soils, that is, beech and wheat rhizospheres (Vosges, France); Burkholderia sp. G5 was selected from acidic and nutrient‐poor podzol soils (Vosges, France). Fe release from clay minerals and production of bacterial metabolites, that is, low molecular weight organic acids (LMWOA) and siderophores, were monitored. Two LMWOA profiles were observed with major gluconate production (> 9000 μM) for Burkholderia sp. G5 and moderate production of lactate, acetate, propionate, formate, oxalate, citrate, and succinate (< 300 μM) for R. aquatilis RA1 and P. agglomerans PA1. HSG demonstrated its usefulness in revealing clay mineral–microorganisms interactions. The effect of bacterial exsudates was clearly separated from physical contact effect.